The Rational - Emotive Approach: A Critique 52 - Morris, G. Barry (Canadian Journal of Counselling and Psychotherapy, 2012)
Certain limitations are apparent in the Rational-Emotive approach postulated by Albert Ellis. These limitations extend to both the theoretical and practical aspects of this psychotherapeutic model. Criticism of this approach can be directed at Ellis' concept of irrationality,analysis of human behavior and therapeutic techniques. The philosophical assumptions underlying Rational-Emotive theory are shown to be restrictive in nature and that irrational thinking may be a necessary step leading to increased personal integration. L'approche Rationnelle-Emotive d'Albert Ellis comporte des limites apparentes. Ces limites concernent tout autant les aspects théoriquesque pratiques de ce modèle psychothérapeutique. La critique de cette approche peut viser le concept d'irrationalité d'Ellis, ainsi que son analyse du comportement humain et ses techniques thérapeutiques. On montre que les postulats philosophiques sous-jacents à la théorie Rationnelle-Emotive sont de nature restrictive et que la pensée irrationnelle peut être une étape nécessaire à l'intégration personnelle.